2020
DOI: 10.3389/fimmu.2020.00968
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Targeted Gene Silencing IDO Synergizes PTT-Induced Apoptosis and Enhances Anti-tumor Immunity

Abstract: Background: Photothermal therapy (PTT) has been demonstrated to be a promising cancer treatment approach because it can be modulated to induce apoptosis instead of necrosis via adjusting irradiation conditions. Recently, an abscopal anti-tumor immunity has been highlighted, in which PTT on the primary tumor also induced repression of distant tumors. In PTT cancer treatments, the mechanism and the role of immune checkpoints to enhance anti-tumor immunity needs to be investigated. Methods: We prepared a multi-fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 44 publications
(84 reference statements)
0
18
0
Order By: Relevance
“…IDO has been proven to catalyze the oxidative catabolism of Trp to Kyn, and regulate immune responses by impairing the survival and activity of T cells 44,45 . IDO has therefore become a therapeutic target for cancer that could either be used alone or in combination with other treatments for tumors 46,47 . However, our results showed that oxaliplatin could inhibit tumor growth and increase the apoptosis of tumor cells, but could also increase the expression of IDO, which might interfere with the therapeutic effect of oxaliplatin.…”
Section: Discussionmentioning
confidence: 99%
“…IDO has been proven to catalyze the oxidative catabolism of Trp to Kyn, and regulate immune responses by impairing the survival and activity of T cells 44,45 . IDO has therefore become a therapeutic target for cancer that could either be used alone or in combination with other treatments for tumors 46,47 . However, our results showed that oxaliplatin could inhibit tumor growth and increase the apoptosis of tumor cells, but could also increase the expression of IDO, which might interfere with the therapeutic effect of oxaliplatin.…”
Section: Discussionmentioning
confidence: 99%
“…GNRs nanoplatforms functionalized with antibodies (Chu et al, 2017), peptides (Singh et al, 2016), proteoglycan, vitamins (Papaioannou et al, 2018;Zhang et al, 2020), and aptamers realize selective targeting via binding to the specific receptors of tumor cells or the TME. To overcome the disadvantages of natural antibodies, such as poor stability, comparably complicated preparation process, and low affinity toward nonimmunogenic targets (Ye and Mosbach 2008), molecular imprinting technology was exploited to construct sialic acid (SA)-imprinted GNRs, which exhibited high affinity to cancer cells overexpressed SA (Yin et al, 2017).…”
Section: Active Targeting Based On the Enhanced Epr Effectmentioning
confidence: 99%
“…IDO is an immunosuppressive factor that can weaken the body's antitumor immunity. This system uses siIDO to silence gene expression to achieve the effect of immunotherapy (Zhang et al, 2020). Although the specificity of PTT is greatly improved, damage to surrounding tissues can be inevitable and trigger certain inflammatory reactions.…”
Section: Combination Of Ptt and Other Therapiesmentioning
confidence: 99%
“…To develop an siIDO platform for in vivo testing Zhang et al developed a folate targeted, gold nanorod based system, for combined siRNA delivery and photothermal therapy [70]. As photothermal therapy elevates the level of IDO, it was speculated that the combination with IDO silencing would result in synergistic effects.…”
Section: Indoleamine 23-dioxygenase 1 (Ido)mentioning
confidence: 99%